2018
DOI: 10.1515/biol-2018-0068
|View full text |Cite
|
Sign up to set email alerts
|

Up-regulation of key glycolysis proteins in cancer development

Abstract: In rapid proliferating cancer cells, there is a need for fast ATP and lactate production, therefore cancer cells turn off oxidative phosphorylation and turn on the so called "Warburg effect". This regulating the expression of genes involved in glycolysis. According to many studies, glucose transporter 1, which supplies glucose to the cell, is the most abundantly expressed transporter in cancer cells. Hexokinase 2, is one of four hexokinase isoenzymes, is also another highly expressed enzyme in cancer cells and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
35
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 37 publications
(36 citation statements)
references
References 80 publications
(150 reference statements)
1
35
0
Order By: Relevance
“…Being structurally similar, the four isoforms vary in expression pattern, cellular localization and properties in regulation. The dominantly expressed among these is HK II which is found to be up-regulated in most of the tissues [16]. Hexokinase II was found to be over-expressed in most cancers leading to enhanced glycolytic rate, which is a phenotype for cancer cells [17].…”
Section: Introductionmentioning
confidence: 99%
“…Being structurally similar, the four isoforms vary in expression pattern, cellular localization and properties in regulation. The dominantly expressed among these is HK II which is found to be up-regulated in most of the tissues [16]. Hexokinase II was found to be over-expressed in most cancers leading to enhanced glycolytic rate, which is a phenotype for cancer cells [17].…”
Section: Introductionmentioning
confidence: 99%
“…In adenocarcinoma, GLUT1 and GLUT3 expression correlate with maximum standardized uptake value (SUV max), but no such correlation was observed for SCC. Neither GLUT1 or GLUT3 expression was correlated with tumor size or 18 F-FDG uptake. 131 RNA-seq and FDG of lung squamous cell carcinoma (LUSC) from patients who underwent surgical resection in correlation to glucose transporters by RNA-seq and immune cell enrichment score (ImmuneScore).…”
Section: Lung Cancersmentioning
confidence: 82%
“…As described earlier, cancer cells cause changes in the expression of genes that code HIF-1, hexokinase 2 (HK2), phosphoglucose isomerase (PG), glyceraldehyde 3-phosphate dehydrogenase, and glucose transporters that are involved in the hypoxic conditions within tumors. Therefore, it is suggested that hypoxia-regulated genes may be a therapeutic target in anticancer therapy [46]. GLUT proteins, such as GLUT1 and GLUT3, and sodiumdependent glucose symporters, such as SGLT1 and SGLT2, are overexpressed in cancers.…”
Section: Glut Proteins As a Target In Anticancer Therapymentioning
confidence: 99%